Birth weight and length in offsprings of mothers with gestational diabetes mellitus due to mutations in GCK gene - Natalia A. Zubkova; Fatima F. Burumkulova; Victoria I. Ulyatovskaya; Vasily A. Petrukhin; Margarita A. Plechanova; Anton E. Panov; Tatiana S. Budykina; Nina A. Makretskaya; Anatoly N. Tiulpakov (Сахарный диабет)
Background. Gestational diabetes (GDM) due to GCK gene mutations is the most frequent form of monogenic diabetes mellitus (DM) presenting during pregnancy. It has been suggested that the use of insulin in pregnancies with fetuses carrying GCK mutations may lead to intrauterine growth retardation. In the present study we evaluated the effect of insulin therapy during pregnancy on birth weight and length in the offsprings of mothers with GDM due to GCK mutations. Aims. The aim was to study birth weight and length in offsprings of mothers with gestational diabetes mellitus due to mutations in GCK, depending on the therapy during pregnancy. Materials and methods. The study included 38 patients with GDM caused by GCK gene mutations (18.7%) and the 45 offsprings. To define molecular basis of GDM in pregnant women we used a targeted NGS. ‘Diabetes panel’ genes were sequenced using a custom Ion Ampliseq gene panel and PGM semiconductor sequencer (Ion Torrent). To found the same mutations in their offsprings was used Sanger sequencing. All children were divided into 3 groups depending of their genotype and therapy received by the mothers during pregnancy. Results. We found statistically significant differences in birth length (p=0.04) and weight (p=0,031) depending on the genotype of the child and therapy in the mother. The risk of macrosomia was shown in non-mutation-carrying offsprings only. The birth weight in children with GCK gene mutations whose mothers received insulin during pregnancy was significantly lower. However, the birth weight remained in the normal range. Conclusions. Since prenatal diagnostics in the mothers with GCK gene mutations is not always justified, we recommend insulin therapy in order to prevent fetal macrosomia, which, however, should be less aggressive than in GDM due to other causes.